Parenting Support: Policy and Practice in the Irish Context. Issue 1 (2nd January 2018) - Connolly, Nuala; Devaney, Carmel
ABSTRACT: Increasing government interest in parenting support has emerged in response to the increasingly diverse form of families, a growing emphasis on children's rights and a policy shift towards prevention and early intervention. This has contributed to a range of stakeholder activity in the area, with the notion that parenting is a set of skills that can be learned now widespread. The need to establish "what works" in parenting support has resulted in considerable research, with evidence supporting the provision of universally accessible supports for all parents which can be tailored for those with additional needs. Simultaneously, an increasing body of evaluation research has resulted in positive evidence-based outcomes for a range of parenting support programmes. This article presents an overview of the policy and practice of parenting support, exploring the international and national literature on what works in improving parental capacity, and detailing the wide-scale emergence of parenting as a policy imperative. The article presents the Irish context, describing the diversity of the population, mapping the current service provision landscape and detailing the strategic direction and emerging parenting support programme of work within Tusla, the statutory Child and Family Agency.